(untitled) (KULT_online, 2014)
In the anthology Ethnologie im 21. Jahrhundert editors Thomas Bierschenk, Matthias Krings, and Carola Lentz provide an overview on contemporary German anthropology. Thirteen articles published by scholars from the fields of anthropology, sociology, cultural and social anthropology, and political science discuss the institutional development of the discipline, the change in epistemic practices and new conditions for fieldwork and methodological approaches. Thereby they suggest self-reflection and self-criticism as key strategies for analysing the current status of German anthropology and its prospects.